2016
DOI: 10.1063/1.4940960
|View full text |Cite
|
Sign up to set email alerts
|

Giant low-field magnetocaloric effect in single-crystalline EuTi0.85Nb0.15O3

Abstract: The magnetocaloric effect in ferromagnetic single crystal EuTi0.85Nb0.15O3 has been investigated using magnetization and heat capacity measurements. EuTi0.85Nb0.15O3 undergoes a continuous ferromagnetic phase transition at TC = 9.5 K due to the long range ordering of magnetic moments of Eu2+ (4f7). With the application of magnetic field, the spin entropy is strongly suppressed and a giant magnetic entropy change is observed near TC. The values of entropy change ΔSm and adiabatic temperature change ΔTad are as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…In this context, it may be noted that undoped and doped EuTiO 3 , EuDy 2 O 4 and GdVO 4 exhibit huge MCE at low temperature. 49,50,[52][53][54] The values of ∆S max m in these compounds are also comparable to the present system. However, for the above mention compounds, ∆S m (T ) shows a strong decrease in the low-temperature region.…”
Section: Resultssupporting
confidence: 84%
“…In this context, it may be noted that undoped and doped EuTiO 3 , EuDy 2 O 4 and GdVO 4 exhibit huge MCE at low temperature. 49,50,[52][53][54] The values of ∆S max m in these compounds are also comparable to the present system. However, for the above mention compounds, ∆S m (T ) shows a strong decrease in the low-temperature region.…”
Section: Resultssupporting
confidence: 84%
“…Substitution by Nb 4+ ion at the Ti 4+ results in the introduction of electrons in EuTiO 3 without disturbing the Eu 2+ moments chain. Previous studies in EuTi 1x Nb x O 3 revealed notable increase in electrical conductivity and large values of magnetocaloric response of about 23.8 J kg −1 K −1 even at low magnetic field 0-2 T [11]. Therefore, introduction of Nb in antiferromagnetic EuTiO 3 results in ferromagnetic behaviour in EuTi 1−x Nb x O 3 (x = 0.15) with T C ∼ 9.5 K and saturation magnetization at 2 K is estimated to be ∼ 7µ B /Eu [11].…”
mentioning
confidence: 88%
“…There has been a considerable amount of theoretical and experimental * goutam@iisermohali.ac.in work done for understanding the nature of the ground state in this family. Among the perovskites, EuTiO 3 with unique divalent rare-earth ion Eu and tetravalent Ti has generated substantial interest since the discovery of magnetoelectric coupling in this compound below the antiferromagnetic (AFM) transition temperature T N = 5.5 K [8][9][10][11][12][13]. EuTiO 3 has a positive Curie-Weiss constant and exhibits strong coupling between magnetic ordering and phonon modes.…”
mentioning
confidence: 99%
“…A few contain precious Rh (e.g., FeRh [24,222,278,279] and Tb 3 Rh [270]). Many contain critical rare earth, such as Eu in Eu 2 In [140], EuTiO 3 [114,135,156,195] doped with Al [113], Cr [196], Mn [134], Co [151], Ni [119], Ba [157,206], Nb [110,170,195] and Eu in other compounds [133,232,240,251]; Gd in GdAlO 3 [158], GdFeO 3 [138,162], GdCrO 3 [183], GdCrO 4 -ErCrO 4 [202], GdScO 3 [117,124], Gd 2 CoMnO 6 [155], Gd 2 BaNiO 5 [152], GdCrTiO 5 [143], GdCo 2 B 2 [271], GdCoC 2 [171], RuSr 2 GdCu 2 O 8 [208], etc. ; Tb in TbFeO 3 [176], TbMn 2 O 5 [179], Tb 2 CoMnO 6 [132], Tb 5 Ge 2−x Si 2−x Mn 2x [255], Tb 4 Gd 1 Si 2.035 Ge 1.935 Mn 0.03 [197], etc.…”
Section: ∆S T T C (K) ∆T S (K)mentioning
confidence: 99%